Genetic Polymorphisms Associated with Thrombotic Disease Comparison of Two Territories: Myocardial Infarction and Ischemic Stroke. (30th October 2019) - Isordia-Salas, Irma; Martínez-Marino, Manuel; Alberti-Minutti, Paolo; Ricardo-Moreno, María Tania; Castro-Calvo, Ricardo; Santiago-Germán, David; Alvarado-Moreno, José Antonio; Calleja-Carreño, Cristian; Hernández-Juárez, Jesús; Leaños-Miranda, Alfredo; Majluf-Cruz, Abraham
Abstract : Background and Purpose . The thrombin-activatable fibrinolysis inhibitor (TAFI) is an important inhibitor of fibrinolysis and plays a critical role in the pathogenesis of arterial thrombosis; genetic polymorphisms of the TAFI gene affect its activity and increase the risk of thrombosis. Moreover, studies in young patients are still scarce. The aim was to examine the contribution of the Thr325Ile and Ala147Thr polymorphisms with ST acute myocardial infarction (STEMI) or idiopathic ischemic stroke (IIS) in the young Mexican population. Methods . A total of 244 patients with STEMI ≤45 years of age and 244 controls. In a second study, 250 patients with IIS ≤45 years of age were recruited, including 250 controls. In both studies, cases and controls were matched by age and sex. The polymorphisms were determined in all participants by PCR-RFLP. Results . There was significant difference in the Thr325Ile genotype distribution (P = 0.001 ) and allele frequency (P = 0.001 ) between STEMI and control groups, but no difference in the Ala147Thr genotype distribution (P = 0.24 ) and allele frequency (P = 0.46 ), neither in the Thr325Ile genotype distribution (P = 0.25 ) nor in the Ala147Thr genotype distribution (P = 0.46 ) or their allele frequencies; there was significant difference between IIS and the control group. There were independent factors for STEMI: the Ile allele (P = 0.01 ), type 2 diabetes mellitus (P = 0.001 ), hypertension (P = 0.001 ), smoking (P = 0.001 ), dyslipidemia (P = 0.001 ), and family history of atherothrombotic disease (P = 0.001 ). The independent factors for IIS were hypertension (P = 0.001 ), smoking (P < 0.01 ), and family history of atherothrombotic disease (P < 0.01 ). Conclusions . The Thr325Ile polymorphism, but no Ala147Thr polymorphism, represents an independent risk factor for STEMI in the young Mexican population.